Analisis Interpersonal Justice dan Store Atmosphere yang Dimediasi oleh Prior Experience terhadap Revisit Intention: (Studi Kasus Café se Kecamatan Cibadak) - Santika, Fidea; Siwiyanti, Leonita; Sudarma, Ade (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of interpersonal justice and store atmosphere on repeat visit intentions, based on customers' previous experiences at cafes in the Cibadak District. The research method employs a quantitative approach, collecting data through questionnaires distributed to café customers, to obtain perception data on fairness, atmosphere, experience, and intention to repeat visits. Data analysis was conducted using statistical techniques to examine the causal relationship between variables and assess the mediating role of customer experience. The results indicate that interpersonal fairness has a positive and significant impact on the customer experience, directly increasing repeat visitor intent. In addition, the store atmosphere also makes a positive contribution indirectly by strengthening the customer experience, but the direct influence of the store atmosphere on visitor intent is not significant. Previous experience has proven to be an important mediator in strengthening the relationship between interpersonal justice and the store atmosphere against repeat visit intentions. The practical implications of these findings highlight the importance of café managers to prioritize the quality of interpersonal interactions and create a comfortable and engaging store atmosphere to maintain customer loyalty. This research contributes theoretically by enriching the service marketing literature, especially in the context of local consumer behavior in the café industry. These findings provide new insights for the development of a holistic, integrated customer experience-based marketing strategy in the face of increasingly fierce business competition.